Effect of Pretreatments and Drying Methods on The Physicochemical and Antioxidant Properties of Whole Eggplant (Solanum aethiopicum) Flour - Anthony Ukom; Dennis Egbujor; Lilian Nwanagba; Immaculata Okparauka (Indonesian Association of Food Technologists, 2023)
Sliced eggplant was pretreated (blanching and citric acid dip), -dried (oven and sun), then pulverized to flour. Physicochemical and antioxidant properties were evaluated using standard methods. The results showed increases in protein, moisture, fat, ash, crude fiber, and carbohydrate contents. They ranged from 7.78–8.39%, 8.90–10.14%, 4.32–5.28%, 0.77–0.91%, 10.72–13.43%, and 63.35–65.77%, respectively. Citric acid treatment and dried methods increased the minerals content for sodium (121.77–125.87 mg/100g), zinc (3.18–5.77 mg/100g), potassium (489.53–628.58 mg/100g), magnesium (68.86–75.39 mg/100g) and iron (8.91–11.82 mg/100g) than the blanched treatment. Functional properties of eggplant flour revealed that bulk density (0.42–0.50%,), oil absorption capacity (0.64–4.85%), and wettability (1.43–4.35%,) increased with citric acid and sun-drying method while swelling index (1.25–1.61%) and water absorption capacity (3.85–5.61%) increased with citric acid and oven drying method. Total polyphenol (26.49–29.78 mg GAE/mL), flavonoid (22.12–11.38 mg QE/mL), ABTS (52.38–61.34 Mmol/100 mL), DPPH (62.78–68.48%) and FRAP (58.67–65.36 Mmol/100mL) showed significant (p<0.05) increases in citric acid and dried methods. From the results, the physicochemical and antioxidant properties of eggplant flour were positively affected by citric acid pre-treatments in sun and oven-dried methods.